2014
DOI: 10.1175/jcli-d-14-00076.1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Pattern of Deep Convective Systems over the Tibetan Plateau–South Asian Monsoon Region Based on TRMM Data

Abstract: Diurnal and seasonal variation, intensity, and structure of deep convective systems (DCSs; with 20-dBZ echo tops exceeding 14 km) over the Tibetan Plateau–South Asian monsoon region from the Tibetan Plateau (TP) to the ocean are investigated using 14 yr of Tropical Rainfall Measuring Mission (TRMM) data. Four unique regions characterized by different orography are selected for comparison, including the TP, the southern Himalayan front (SHF), the South Asian subcontinent (SAS), and the ocean. DCSs and intense D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
117
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 49 publications
9
117
0
Order By: Relevance
“…6d). Romatschke et al (2010) and Qie et al (2014) investigated the increase of extreme convection over the Tibetan Plateau during the monsoon season and indicated that the westerly winds and high relative humidity are likely related to the formation of systems in this region. During the monsoon season, westerly winds weaken gradually from May to August, and relative humidity increases westward from the eastern Tibetan Plateau.…”
Section: B Interannual and Monthly Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…6d). Romatschke et al (2010) and Qie et al (2014) investigated the increase of extreme convection over the Tibetan Plateau during the monsoon season and indicated that the westerly winds and high relative humidity are likely related to the formation of systems in this region. During the monsoon season, westerly winds weaken gradually from May to August, and relative humidity increases westward from the eastern Tibetan Plateau.…”
Section: B Interannual and Monthly Variabilitymentioning
confidence: 99%
“…The third type of monthly variation is the persistent high frequency of MCS occurrence, which means that there are regions where the MCS occurrences are persistently active during the warm seasons compared to the others. Those regions include the Bay of Bengal, regions south of the Himalayas, and the northern Indo-China (Houze 2007;Romatschke et al 2010;Xu and Zipser 2011;Qie et al 2014). Figure 7 illustrates the monthly variability of the six MCS types.…”
Section: B Interannual and Monthly Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan and Qie (2008) explored the south China sea before and after the onset of the summer monsoon. Qie et al (2014) observed the deep and intense deep convective clouds over Tibetan Plateau-South Asian monsoon using 40 dBZ crossing 10 and 14 km altitude respectively. Bhat and Kumar (2015) observed a close similarity in vertical profiles over land and oceanic areas in cumulonimbus towers over south Asian areas during Indian summer monsoon.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies consider the 40 dBZ at and above 10 km to observe the vertical structure in convective precipitation (Houze et al, 2007;Qie et al, 2014;Romatschke & Houze, 2010;Romatschke et al, 2011a;2011b). Previous criteria underestimate some intense clouds, which evolve near the surface, but are not very deep (>10 km).…”
Section: Introductionmentioning
confidence: 99%